2014
DOI: 10.17221/192/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the transgenic CrylAc and CpTI insect-resistant cotton SGK321 on rhizosphere soil microorganism populations in northern China

Abstract: Transgenic CrylAc and CpTI insect-resistant cotton SGK321 has been widely adopted for many years in several regions of China, however the understanding of its potential effects on soil microorganisms is limited. The impact of transgenic cotton SGK321 on microorganism populations in rhizosphere soil was investigated. The numbers of bacteria, fungi, and actinomycetes were measured by counting colony-forming units after incubation on appropriate medium in a two-year field study in the northern China. Rhizosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Sarkar et al (2008) evaluated the soil microbial activity, and found a significant reduction in dehydrogenase activity (17%) and soil respiration (3.5%) in a Bt-cotton rhizosphere compared with a non-Bt isoline. These results differ from those obtained by Li et al (2011), Velmourougane andSahu (2014), andZhang et al (2014), where transgenic cotton had no impact on microbial populations. According to Romeis et al (2006), the Bt technology is more specific and provides fewer environmental damages and collateral effects on parasitoids and predators than most insecticides currently used, which justifies its adoption due to the significant reduction in the number of applications.…”
Section: Transgenic Cotton For Insect Resistancecontrasting
confidence: 99%
See 1 more Smart Citation
“…Sarkar et al (2008) evaluated the soil microbial activity, and found a significant reduction in dehydrogenase activity (17%) and soil respiration (3.5%) in a Bt-cotton rhizosphere compared with a non-Bt isoline. These results differ from those obtained by Li et al (2011), Velmourougane andSahu (2014), andZhang et al (2014), where transgenic cotton had no impact on microbial populations. According to Romeis et al (2006), the Bt technology is more specific and provides fewer environmental damages and collateral effects on parasitoids and predators than most insecticides currently used, which justifies its adoption due to the significant reduction in the number of applications.…”
Section: Transgenic Cotton For Insect Resistancecontrasting
confidence: 99%
“…Prado et al (2014) conducted an extensive review on the development of transgenic plants and described several phases involved from the initial concept to the release of the commercial product. The whole process may be summarized in consecutive procedures as follows: product concept (1), gene discovery (2), evaluation (3), event selection (4), variety development (5), regulatory process (6), field production (7), and commercial release (8). These procedures are distributed in five main phases: gene discovery and identification, genetic transformation, early development, advanced development, and prelaunch and launch.…”
Section: Introductionmentioning
confidence: 99%
“…The potato plant growth stage and field location affected the soil enzyme activities more than the starch modification of tubers [100]. Compared to harvest year, plant growth stage and cotton cultivar, the pest resistance trait had a negligible effect on the activities of DHA, urease and phosphatase in soil [67]. The year and stage of growth significantly affected the urease, DHA and sucrase activities in the field trials of virus-resistant wheat [82].…”
Section: Factors Influencing the Interaction Of Transgenic Plants Wit...mentioning
confidence: 98%
“…Esses resultados podem, inicialmente, indicar que o tempo de condução experimental (103 dias) foi insuficiente para que evidenciasse o efeito da transgenia do milho Bt nos demais tratamentos relacionados ou não a FMAs, já que a mesma está relacionada, em condições de campo, à resistência a pragas, doenças e maior produção (Bobrowski et al, 2003). No entanto, em estudos anteriores, que conduziram experimentos também em curto prazo, avaliando o efeito de plantas geneticamente modificadas na microbiota do solo, não observaram alterações em atributos como densidade de bactérias, fungos e actinobactérias em solo rizosférico de algodão (Zhang et al, 2014), assim como Saxena & Stotzky (2001) que não observaram efeitos do milho Bt (Cry1Ab) na densidade total de microrganismos do solo, por um período de 40 dias.…”
Section: Horizontesunclassified